PENGEMBANGAN SISTEM APLIKASI MANAJEMEN PROPERTI BAGIAN PENYEWAAN UNIT (STUDI KASUS: PT. SATRAND GROUP INDONESIA) - Christianto, Kevin; Andry, Johanes Fernandes; Geasela, Yemima Monica; Tanardi, Indra (Infotech: Journal of Technology Information, 2023)
PT. Satrand Group Indonesia is a daily rental company, daily apartments, transit rentals, transit apartments, grand kamala lagoon daily rentals, grand kamala lagoon daily apartments, east center daily rentals, east center daily apartments, Gading Nias daily apartments, Gading Nias daily rentals, apartments Bekasi daily rental, Bekasi daily rental, Bekasi lodging. In carrying out its activities, this company still uses the process of ordering units directly and through contact admins. So that customers who will rent are required to come and see or make sure the unit is available or not directly to place an order. The purpose of this research is to build a unit rental management information system at PT. Satrand Group Indonesia uses the waterfall method. This research has resulted in a unit rental management information system at PT. Satrand Group Indonesia which makes it easy for customers to place orders, makes it easier for customers to get information about units and makes it easier to make reports.